2023
DOI: 10.1002/anie.202311879
|View full text |Cite
|
Sign up to set email alerts
|

Aldol Condensation for the Construction of Organic Functional Materials

Xiuyuan Zhu,
Jiayao Duan,
Junxin Chen
et al.

Abstract: Aldol condensation is a cost‐effective and sustainable method, offering advantages of low complexity, substrate universality, and high efficiency. Over the past decade, it has become popular for creating next‐generation organic functional materials, particularly rigid rod conjugated (semi)conductors. This review focuses on conjugated small‐molecules, oligomers and polymeric (semi)conductors synthesized through aldol condensation, with emphasis on their remarkable features in advancing n‐type organic field‐effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…[32] Recently, metal-free aldol condensation has been successfully demonstrated during the syntheses of various fused n-type polymeric, small molecular, and oligomeric OMIECs. [33] Particularly, the aldol condensation represents a low-cost, sustainable approach without using any expensive metals, and produces water as the only by-product. Aldol poly(condensation) reactions typically feature lactone/lactam rings joining together via C═C bond with the entire structure showing rigid rod-like motif, which is beneficial for electronic conduction pathway.…”
Section: General Synthetic Methods Of N-type Omiecs For Oectsmentioning
confidence: 99%
“…[32] Recently, metal-free aldol condensation has been successfully demonstrated during the syntheses of various fused n-type polymeric, small molecular, and oligomeric OMIECs. [33] Particularly, the aldol condensation represents a low-cost, sustainable approach without using any expensive metals, and produces water as the only by-product. Aldol poly(condensation) reactions typically feature lactone/lactam rings joining together via C═C bond with the entire structure showing rigid rod-like motif, which is beneficial for electronic conduction pathway.…”
Section: General Synthetic Methods Of N-type Omiecs For Oectsmentioning
confidence: 99%
“…Based on the fusion between organic electrochemical transistor (OECT) and photoelectrochemistry (PEC), the newly emerged organic photoelectrochemical transistor (OPECT) composing three terminals of photoresponsive gate (G), source (S), and drain (D) have shown substantial potential in the development of next-generation organic devices with intrinsic signal amplification, temporal-spatial light controllability, and diverse applications in, e.g., bioanalysis, , optoelectronics, and neuromorphic engineering. , Principally, according to different signaling mechanisms stemming from the pristine doping state of the conducting channels, existing OPECT operations could be divided into depletion and accumulation modes. Light impact on specific photogates could induce additional photopotential and alter the potential distribution of the two solid–liquid interfaces. Previous studies have revealed that photoanodes generating positive photovoltage are more suitable for depletion-mode channels, while photocathodes generating negative photovoltage are more suitable for accumulation-mode channels. These studies hinted at an either-or situation yet ignored another possibility: could both the photoanode and photocathode be simultaneously utilized for enhanced OPECT bioanalysis?…”
Section: Introductionmentioning
confidence: 99%
“…While the development of high-performance n -type conducting polymers has made significant strides in recent years, it often entails the use of toxic organotin reagents, nonrecyclable precious metal catalysts (e.g., Pd), and the use of harmful solvents like chlorobenzene, tetrahydrofuran, and dimethylformamide (Figure S1b–e). Furthermore, these challenges extend beyond the synthetic stage, with many n -type conducting polymers requiring flammable or hazardous solvents during processing. , These limitations have constrained their potential for commercial and industrial deployment.…”
Section: Introductionmentioning
confidence: 99%